2021
DOI: 10.1111/acem.14217
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 viral load in nasopharyngeal swabs in the emergency department does not predict COVID‐19 severity and mortality

Abstract: Introduction: The ongoing COVID-19 pandemic has led to devastating repercussions on health care systems worldwide. This viral infection has a broad clinical spectrum (ranging from influenza-like disease, viral pneumonia, and hypoxemia to acute respiratory distress syndrome requiring prolonged intensive care unit stays). The prognostic impact of measuring viral load on nasopharyngeal swab specimens (by reverse transcriptase polymerase chain reaction [RT-PCR]) is yet to be elucidated. Methods: Between March 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
0
29
1
1
Order By: Relevance
“…Our most striking observation was an approximately billion-fold variation in SARS-CoV-2 viral loads. While the predictive value of viral loads for clinical outcomes or treatment response is unclear, with several studies reporting significant [28][29][30][31][32][33], minimal [34,35] or no [36][37][38] associations with increased severity or mortality from COVID-19, we report significant independent associations of pre-treatment variables such as invasive ventilation and immunosuppression with higher viral loads in our cohort that may subsequently influence their response to treatment (Table 2A; Fig. 1C).…”
Section: Discussionmentioning
confidence: 67%
“…Our most striking observation was an approximately billion-fold variation in SARS-CoV-2 viral loads. While the predictive value of viral loads for clinical outcomes or treatment response is unclear, with several studies reporting significant [28][29][30][31][32][33], minimal [34,35] or no [36][37][38] associations with increased severity or mortality from COVID-19, we report significant independent associations of pre-treatment variables such as invasive ventilation and immunosuppression with higher viral loads in our cohort that may subsequently influence their response to treatment (Table 2A; Fig. 1C).…”
Section: Discussionmentioning
confidence: 67%
“…Nonetheless, in our cohort, SARS-CoV-2 RNA levels were not associated with the clinical outcome at any time point. There are some controversial data regarding this issue, while some studies have not reported any association between SARS-CoV-2 viral load during acute infection and COVID-19 severity [11,12] others point out that elevated viral load could be used to identify patients at higher risk for morbidity or severe COVID-19 outcome [13,14]. The controversial results might be explained for the heterogeneity of the studies related to the different characteristics of the study population and/or the methodology used for SARS-CoV-2 quantification and sampling quality (i.e., normalization using copies/cells).…”
Section: Discussionmentioning
confidence: 99%
“…In diseases caused by viral infections, viruses and hosts can contribute to disease heterogeneity. Studies have found that SARS-CoV-2 has limited genetic variation and stable evolution (17,18), suggesting that viral genetic variation and evolution might contribute to infectivity and fatality (19,20). However, not so much correlation is noted to the heterogeneity of COVID-19 (17,(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%